2017
DOI: 10.1038/srep40932
|View full text |Cite
|
Sign up to set email alerts
|

The Fecal Microbial Community of Breast-fed Infants from Armenia and Georgia

Abstract: Multiple factors help shape the infant intestinal microbiota early in life. Environmental conditions such as the presence of bioactive molecules from breast milk dictate gut microbial growth and survival. Infants also receive distinct, personalized, bacterial exposures leading to differential colonization. Microbial exposures and gut environmental conditions differ between infants in different locations, as does the typical microbial community structure in an infant’s gut. Here we evaluate potential influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 77 publications
1
20
1
Order By: Relevance
“…Similarly, the association between the secretory status of mothers (affecting the abundance of 2=-fucosylated HMOs) and the abundance of B. longum subsp. infantis in breastfed infants, as originally observed in a U.S. cohort (39), could not be replicated in a study performed in Armenia and Georgia (40). Adding to our results obtained in two European countries, this observation suggests geography-related specificities of the infant gut bifidobacterial population in its ability to utilize HMOs.…”
Section: Discussioncontrasting
confidence: 88%
“…Similarly, the association between the secretory status of mothers (affecting the abundance of 2=-fucosylated HMOs) and the abundance of B. longum subsp. infantis in breastfed infants, as originally observed in a U.S. cohort (39), could not be replicated in a study performed in Armenia and Georgia (40). Adding to our results obtained in two European countries, this observation suggests geography-related specificities of the infant gut bifidobacterial population in its ability to utilize HMOs.…”
Section: Discussioncontrasting
confidence: 88%
“…Indeed, Lewis et al [34] reported that Bifidobacterium strains that are able to utilize 2 -FL are enriched in the stools of the infants receiving breast milk of secretors, compared to those of non-secretors. Several previous studies showed that the bifidobacterial population increases more rapidly and abundantly in infants fed by secretor mothers than those fed by non-secretor mothers [34,78,79]. Two FL transporters we mentioned above can import both 2 -FL and 3-FL [40]; therefore, bifidobacteria carrying the transporters can adapt to FL from both secretors and non-secretors.…”
Section: Milk Oligosaccharide Composition May Dictate Transporter-drimentioning
confidence: 90%
“…Studies have shown that breastfeeding is associated with higher levels of Bifidobacterium 1,2,16 , which is consistent with our study. The genus Bifidobacterium possesses multiple benefits, such as modulation of the immune system, production of vitamins, remission of atopic dermatitis symptoms in infants and decrease in rotavirus infections and lactose intolerance in children and adults 10,17 . Bifidobacteria is reported to be associated with diminished risk of allergic diseases 18 and excessive weight gain 19 .…”
Section: Discussionmentioning
confidence: 99%